Comparison of the Protective Effects of Ginsenosides Rb1 and Rg1 on Improving Cognitive Deficits in SAMP8 Mice Based on Anti-Neuroinflammation Mechanism - Yang, Yujie; Li, Shanshan; Huang, Hong; Lv, Jingwei; Chen, Shanguang; Pires Dias, Alberto Carlos; Li, Yujiao; Liu, Xinmin; Wang, Qiong (Frontiers in Pharmacology, 2020)
This present study was designed to investigate the different effects of ginsenosides Rb1 and Rg1 on improving cognitive deficits in 4-month-old SAMP8 mice. Mice were divided into six groups, including the SAMP8 group, the SAMP8 + Donepezil (1.6 mg/kg) group, the SAMP8 + Rb1 (30 and 60 µmol/kg), and SAMP8 + Rg1 (30 and 60 µmol/kg) groups. SAMR1 mice of the same age were used as the control group. Ginsenosides and donepezil were administrated orally to animals for 8 weeks, then the learning and memory ability of mice were measured by using Morris water maze (MWM) test, object recognition test and passive avoidance experiments. The possible mechanisms were studied including the anti-glial inflammation of Rb1 and Rg1 using HE staining, immunohistochemistry and western blot experiments. Results revealed that Rb1 and Rg1 treatment significantly improved the discrimination index of SAMP8 mice in the object recognition test. Rb1 (60 µmol/kg) and Rg1 (30, 60 µmol/kg) could significantly shorten the escape latency in the acquisition test of the MWM test in SAMP8 mice. Furthermore, Rb1 and Rg1 treatments effectively reduced the number of errors in the passive avoidance task in SAMP8 mice. Western blot experiments revealed that Rb1 showed higher effect than Rg1 in decreasing protein expression levels of ASC, caspase-1 and Aβ in the hippocampus of SAMP8 mice, while Rg1 was more effective than Rb1 in decreasing the protein levels of iNOS. In addition, although Rb1 and Rg1 treatments showed significant protective effects in repairing neuronal cells loss and inhibiting the activation of astrocyte and microglia in hippocampus of SAMP8 mice, Rb1 was more effective than Rg1. These results suggest that Rb1 and Rg1 could improve the cognitive impairment in SAMP8 mice, and they have different mechanisms for the treatment of Alzheimer's disease.